2005
DOI: 10.1002/bjs.5106
|View full text |Cite
|
Sign up to set email alerts
|

Cancer surveillance in ulcerative colitis

Abstract: Rates of detection of dysplasia can be improved by chromoendoscopy. Molecular genetics has the potential to identify patients most at risk of cancer and can differentiate between different types of lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 73 publications
1
37
0
6
Order By: Relevance
“…Previous studies in Western countries have reported that UC-CRC often presents as a mucinous or of signet-ring cell type, and it is multiple and more uniformly distributed throughout the colon than sporadic CRC. 37,38 Consistent with these findings, the present study showed that mucinous or signet ring cell type cancer accounted for 17% of the UC-CRCs, which was almost four times higher than among the sporadic CRCs. Furthermore, in 11% of the UC-CRC cases there were multiple lesions, a rate that was almost twice as high as among the sporadic CRC cases.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies in Western countries have reported that UC-CRC often presents as a mucinous or of signet-ring cell type, and it is multiple and more uniformly distributed throughout the colon than sporadic CRC. 37,38 Consistent with these findings, the present study showed that mucinous or signet ring cell type cancer accounted for 17% of the UC-CRCs, which was almost four times higher than among the sporadic CRCs. Furthermore, in 11% of the UC-CRC cases there were multiple lesions, a rate that was almost twice as high as among the sporadic CRC cases.…”
Section: Discussionsupporting
confidence: 93%
“…Chronic inflammation and cancer have been linked since the 1850s and current thought has it as a major contributor to cancer pathogenesis. For example, inflammatory bowel diseases such as ulcerative colitis and Crohn's diseases are associated with an increased risk of colorectal cancer [34,35]. Individuals with ulcerative colitis have a 10-fold greater risk of developing colorectal cancer compared to the risk defined for the general population [36][37][38].…”
Section: C1 the Immune System Is Linked To Tumor Development And Prmentioning
confidence: 99%
“…Colorectal cancer is one of the most serious complications of inflammatory bowel disease (IBD), including ulcerative colitis and Crohn's disease. The relative risk of colorectal cancer in patient with colitis is two to eight times that of the general population (1). Although it is clear that chronic inflammation is a risk factor of colorectal cancer, the pathogenesis of colitis-associated cancer (CAC) is still uncertain.…”
Section: Introductionmentioning
confidence: 99%